Pemanfaatan Konsep Diferensial Dalam Strategi Pengembangan Bisnis - Huda Firdausyi, Wantech Arofiq; Nursanti, Yuli Bangun (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
Basic mathematical concepts in economics are crucial in learning economic mathematics. One fundamental mathematical concept used in the field of economics is differential calculus. By utilizing differentials, business owners can make calculated decisions based on data, allowing them to make decisions that benefit the company. This research employs a systematic literature review and differential mathematics theory, specifically the Susceptible-Infected-Recovered (SIR) model, to measure the effectiveness of applying differential concepts in business development strategies.